2022
DOI: 10.3390/ani12243527
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of the Most Frequently Observed Histological Changes in Duodenal and Rectal Mucosal Biopsies in Horses with Recurrent Colic

Abstract: Colic, a condition affecting the gastrointestinal tract of horses, manifests as severe pain and may be a life-threatening condition. It is possible to distinguish between an acute, disposable process, as well as recurrent colic symptoms (abdominal pain) caused by an ongoing chronic inflammatory process. This paper presents a retrospective analysis of the histopathological findings of duodenal and rectal samples taken from horses with recurrent colic, with the aim to determine the frequency and extent of inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The previous studies by Bowden et al [1] and Purnama et al [16] have also demonstrated that colic symptoms might be accompanied by symptoms such as pale and congestion-ridden mucous membranes, severe dehydration, bowel movement, loss of eating habits, rapid heartbeat per minute, abundant sweat, excessive urine, and rising body temperature. HR, stomach reflux, packed cell volume, capillary refill time, and color of mucous membranes-which can range from cyanotic to brick red-have all been linked favorably in a number of cases involving horses diagnosed with colic [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The previous studies by Bowden et al [1] and Purnama et al [16] have also demonstrated that colic symptoms might be accompanied by symptoms such as pale and congestion-ridden mucous membranes, severe dehydration, bowel movement, loss of eating habits, rapid heartbeat per minute, abundant sweat, excessive urine, and rising body temperature. HR, stomach reflux, packed cell volume, capillary refill time, and color of mucous membranes-which can range from cyanotic to brick red-have all been linked favorably in a number of cases involving horses diagnosed with colic [17].…”
Section: Discussionmentioning
confidence: 99%
“…The season is one of them, together with several management and risk factors specific to horses, such as age, gender, breed, wind-sucking habits, parasites, nutritional status and feeding practices, physical activity, access to housing and pasture, availability of water, movement, and vaccination. According to these results, colic is a complex condition, and recurrent colic is more likely to occur in horses who have already experienced one episode [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The least commonly reported type of IBD in horses used to be lymphocytic–plasmacytic enterocolitis (LPE) [ 1 ]. In the more recent literature, however, it appears that LPE is the most common form of IBD [ 5 , 12 ]. LPE causes weight loss, variable diarrhea, depression, recurrent colic and inappetence [ 2 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Mucosal biopsies obtained by endoscopy of the duodenum or directly through a transrectal approach have the advantage of being less invasive than an open surgical approach but have low diagnostic sensitivity, with only 20%-56% of biopsies providing an accurate identification of the disease process. 2,[9][10][11] Biopsy samples obtained by ventral midline celiotomy or flank laparotomy have a better diagnostic value 4,12 but also have increased risk of postoperative complications including incisional infections, peritonitis, and patient discomfort in comparison with endoscopic procedures. 4,[11][12][13][14] Advances in laparoscopic techniques for exploration of the abdomen have led to the development of minimally invasive techniques to obtain full thickness biopsy samples.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal biopsies in the horse are used in both clinical applications and research to obtain representative samples for identification of changes in intestinal architecture, and infectious or infiltrative disease processes 1–8 . Mucosal biopsies obtained by endoscopy of the duodenum or directly through a transrectal approach have the advantage of being less invasive than an open surgical approach but have low diagnostic sensitivity, with only 20%–56% of biopsies providing an accurate identification of the disease process 2,9–11 . Biopsy samples obtained by ventral midline celiotomy or flank laparotomy have a better diagnostic value 4,12 but also have increased risk of postoperative complications including incisional infections, peritonitis, and patient discomfort in comparison with endoscopic procedures 4,11–14 …”
Section: Introductionmentioning
confidence: 99%